Dynamic behaviour of single droplets impinging upon liquid films with variable thickness: Jet a-1 and hvo mixtures - Ribeiro, Daniela (2018)
Fortunately, the human being has already started to be environmentally concerned and the search for new alternatives to reduce pollution increased. Transports are responsible for a significant portion and it is extremely necessary to bet on alternatives to oil. The introduction of biofuels in aero-engines could be an example. In order to modify and optimize piston engines and gas turbines to operate efficiently with alternative fuels, this work used Jet Fuel and Biofuel mixtures. The focus of these studies was to visualize the dynamic behavior of single droplets impinging upon liquid films with variable thickness. The existence of splash as well as its characteristics were reported and the differences and similarities between the outcomes according to the impact conditions and the fluid properties were catalogued. To achieve that an experimental facility was designed and built. Four fluids were tested: water (as reference), 100% Jet A-1, 75%/25% and 50%/50% mixtures of Jet A-1 and HVO (Hydro-processed Vegetable Oil), respectively, since civil aviation only accept mixtures with at least 50% Jet Fuel in volume. The fluid properties were measured to ensure accuracy. The liquid film depths considered were 10%, 50% and 100% of the droplet diameter. A high-speed digital camera was used to image acquisition and the droplet was released by a syringe pump connected to the needle at a specific pumping rate. The impact surface was a perspex container filled with fluid. Five needles with different inner diameters and three impact heights were employed to provide a variety of Weber and Reynolds numbers.